2022
DOI: 10.2174/0929867329666220401103643
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Carvacrol on In Vitro Models of Metabolically-Associated Liver Steatosis and Endothelial Dysfunction: A Role for Fatty Acids in Interfering with Carvacrol Binding to Serum Albumin

Abstract: Background: Carvacrol, a plant phenolic monoterpene, is largely employed as food additive and phytochemical. Objective: We aimed to assess the lipid lowering and protective effects of carvacrol in vitro using cellular models of hepatic steatosis and endothelial dysfunction. We also investigated if and how the binding of carvacrol to albumin, the physiological transporter for small compounds in the blood, might be altered by the presence of high levels of fatty acids (FAs). Methods: Hepatic FaO cells treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…41 Carvone might exert hepatoprotective effects by competing with fatty acids for binding to albumin, thereby reducing lipid accumulation and oxidative stress in hepatocytes. 42 1,8-Cineole could treat steatosis and fibrosis in mice liver by inactivating the Akt/PI3-kinase pathway. 43 In addition, α-Terpineol could reduce the content of malondialdehyde in liver tissue in a dose-dependent manner, reducing oxidative stress and histopathology of the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Carvone might exert hepatoprotective effects by competing with fatty acids for binding to albumin, thereby reducing lipid accumulation and oxidative stress in hepatocytes. 42 1,8-Cineole could treat steatosis and fibrosis in mice liver by inactivating the Akt/PI3-kinase pathway. 43 In addition, α-Terpineol could reduce the content of malondialdehyde in liver tissue in a dose-dependent manner, reducing oxidative stress and histopathology of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…β‐Caryophyllene reduced pro‐inflammatory mediators such as TNF‐α, IL‐1β, IL‐6, chain enhancers of NF‐κB, thereby improving liver disease characterized by inflammation and oxidative stress 41 . Carvone might exert hepatoprotective effects by competing with fatty acids for binding to albumin, thereby reducing lipid accumulation and oxidative stress in hepatocytes 42 . 1,8‐Cineole could treat steatosis and fibrosis in mice liver by inactivating the Akt/PI3‐kinase pathway 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The protective and lipid‐lowering effects of carvacrol in hepatic steatosis (cellular models) and endothelial dysfunction indicated that exposure of cells (endothelial HECV cells) with carvacrol counteracted lipid accumulation in hepatocytes and secured endothelial cells from dysfunction and oxidative stress (Khalil et al., 2022 ). Treatment with carvacrol (0.03–3 μM) remarkably inhibited platelet‐derived growth factor (PDGF)‐BB‐stimulated rat aortic smooth muscle cells proliferation and migration.…”
Section: Resultsmentioning
confidence: 99%
“…The protective and lipid-lowering effects of carvacrol in hepatic steatosis (cellular models) and endothelial dysfunction indicated that exposure of cells (endothelial HECV cells) with carvacrol counteracted lipid accumulation in hepatocytes and secured endothelial cells from dysfunction and oxidative stress (Khalil et al, 2022).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…CVL has gained attention among the scientific community due to its diverse biological activities and its potential health benefits [ 21 , 22 , 23 ]. CVL exerts antimicrobial [ 24 ], antioxidant [ 25 ], anti-inflammatory [ 26 ], and antisteatotic effects [ 27 ], and is being explored for various pharmacological and nutraceutical applications.…”
Section: Introductionmentioning
confidence: 99%